Institutional Environment and the Strategies of the Firms of the Brazilian Electricity Industry - Leite, Andre Luis da Silva; Nunes, Nei Antonio (International Journal of Energy Economics and Policy, 2020)
The main goal of this paper is to analyze how the evolution of the institutional environment of the Brazilian Electricity Industry (BEI) has influenced the strategies of the firms. The main characteristics of the BEI are: almost 90% the electricity is generated from hydroelectric plants; central coordination is required to minimize costs, optimize the operation of the system and mitigate risks; hybrid governance structure, where private firms compete with public owned firms; specific assets; and a complex and uncertain business environment. Since 1996, the BEI has faced two distinct reforms. The first, more market oriented, was characterized by the privatization of 80% of distribution firms and 20% of generation assets. But in 2001 Brazil faced its worse electricity crisis in history, so the new government in 2003 proposed a new model for the BEI. This model re-established the role of the government as a planner and tried to create a more competitive market through auctions. We analyze the long term contracts to buy energy and new investments in generation in the BEI. We show that in Brazil there were risks of gaming and it is difficult to allocate the residual rights perfectly and this has an influence in the fact that firms are buying electricity from firms of the same economic group. We conclude that the industry characteristics, the evolution of its governance structure and the transition between institutional models lead to an elevated potential for vertical integration. Keywords: Brazilian Electricity Industry – Transaction costs economics – Vertical integration JEL Classifications: D23, L94 DOI: https://doi.org/10.32479/ijeep.9907